2019
DOI: 10.1002/bdd.2182
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐specific altered nicotine metabolism in 3,3′‐diindolylmethane (DIM) exposed mice

Abstract: Two indole compounds, indole‐3‐carbinol (I3C) and its acid condensation product, 3,3′‐diindolymethane (DIM), have been shown to suppress the expression of flavin‐containing monooxygenases (FMO) and to induce some hepatic cytochrome P450s (CYPs) in rats. In liver microsomes prepared from rats fed I3C or DIM, FMO‐mediated nicotine N‐oxygenation was decreased, whereas CYP‐mediated nicotine metabolism to nicotine iminium and subsequently to cotinine was unchanged. Therefore, it was hypothesized that in mice DIM wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Recently, the vitro rate of CYP2A5-catalyzed oxidation of nicotine to nicotine-iminium ion (Fig. 1) was shown to exhibit a higher median, as well as a larger inter-animal variability, in female than in male nicotine-injected C57BL/6 mice (Bloom et al, 2019). Our present finding that CYP2A5 activity is higher in female than in male mice (N = 8 for each sex) is in accord with these recent reports.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the vitro rate of CYP2A5-catalyzed oxidation of nicotine to nicotine-iminium ion (Fig. 1) was shown to exhibit a higher median, as well as a larger inter-animal variability, in female than in male nicotine-injected C57BL/6 mice (Bloom et al, 2019). Our present finding that CYP2A5 activity is higher in female than in male mice (N = 8 for each sex) is in accord with these recent reports.…”
Section: Discussionsupporting
confidence: 92%
“…In females, an additional mechanism of regulation of CYP2A5/CYP2A4, viz by female hormones, may occur. It has been suggested that the observed wider ranges of CYP2A5/CYP2A4 protein levels and of the in vitro C-oxidation rates in female C57BL/6 mice compared to male mice [ 14 , 15 ] is due to the effect of female sex hormones, estradiol and progesterone, whose concentrations vary during the estrous cycle of 3–4 days [ 25 , 26 ]. Although we did not examine possible effects of the estrous cycle on the rate of cotinine formation, the current result is less likely to be largely affected by fluctuations in female hormone levels because we collected samples from five mice that received nicotine for seven days, which encompass most if not all phases of the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of nicotine-∆5′(1′)-iminium ion, mediated by CYP2A5, is the first step in the formation of cotinine. The in vitro rate of iminium ion formation is significantly faster in female-derived liver microsomes than in their male counterparts [ 9 , 14 ]. These observations strongly suggest that, in vitro, nicotine is metabolized to cotinine at a faster rate in female than in male C57BL mice.…”
Section: Introductionmentioning
confidence: 99%